2020
DOI: 10.3350/cmh.2018.0073
|View full text |Cite
|
Sign up to set email alerts
|

Serum Wisteria floribunda agglutinin-positive human Mac-2 binding protein level predicts recurrence of hepatitis B virus-related hepatocellular carcinoma after curative resection

Abstract: Background/Aims: To investigate whether serum Wisteria floribunda agglutinin-positive human Mac-2-binding protein (WFA + -M2BP) can predict the recurrence of hepatitis B virus (HBV)-related hepatocellular carcinoma (HCC) after curative resection. Methods: Patients with chronic hepatitis B (CHB) who underwent curative resection for HCC between 2004 and 2015 were eligible for the study. Recurrence was sub-classified as early (<2 years) or late (≥2 years). Results: A total of 170 patients with CHB were selected. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 31 publications
0
20
0
Order By: Relevance
“…Thus, M2BPGi level reflects not only liver fibrosis but also liver function. M2BPGi level is also associated with recurrence and prognosis after hepatectomy and can be used for follow-up after HCC therapy [92][93][94]. Sarcopenia has recently attracted attention as a complication of cirrhosis.…”
Section: Utility Of M2bpgi In Cirrhosismentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, M2BPGi level reflects not only liver fibrosis but also liver function. M2BPGi level is also associated with recurrence and prognosis after hepatectomy and can be used for follow-up after HCC therapy [92][93][94]. Sarcopenia has recently attracted attention as a complication of cirrhosis.…”
Section: Utility Of M2bpgi In Cirrhosismentioning
confidence: 99%
“…M2BPGi levels increase as the disease progresses. M2BPGi can be used to assess disease status, such as that of liver fibrosis [ 31 38 , 52 58 , 71 75 ], HCC risk [ 31 , 32 , 36 , 48 51 , 53 , 58 , 62 69 , 79 , 104 ], HCC recurrence risk [ 92 94 ], liver function [ 82 , 87 91 ], and prognosis of chronic liver diseases [ 82 86 ], with progression of the disease. In one relevant meta-analysis, the sensitivities and specificities for predicting significant fibrosis (≥F2), advanced fibrosis (≥F3), and cirrhosis were 0.690, 0.764, and 0.818 and 0.778, 0.758, and 0.839, respectively [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…In patients with undetectable HBV DNA during NA therapy, higher pre-treatment M2BPGi level was associated with increased risk of HCC development. 83,85 Cheung et al 85 85 In patients with HBV-related HCC, Kim et al 86 showed that the level of M2BPGi is an independent predictive factor of HBV-relat-ed HCC recurrence after curative resection. Also, Heo et al 87 evaluated its accuracy in assessing liver fibrosis and in predicting the risk of developing HCC in patients with CHB.…”
Section: M2bpgi For Hcc Prediction In Chbmentioning
confidence: 99%
“…In patients with HBV-related HCC, Kim et al [ 86 ] showed that the level of M2BPGi is an independent predictive factor of HBV-related HCC recurrence after curative resection. Also, Heo et al [ 87 ] evaluated its accuracy in assessing liver fibrosis and in predicting the risk of developing HCC in patients with CHB.…”
Section: Liver Fibrosis Marker: M2bpgimentioning
confidence: 99%
“…For the prediction of HCC, a total of 8 studies with 2,240 participants were selected ( Table 2). Among them, 4 studies reported the occurrence of HCC after antiviral treatment or HBeAg seroconversion 49,50,55,56 , one study discussed the reoccurrence of HCC after curative resection 54 , and 3 studies focused on the development of HCC [51][52][53] . The WFA+-M2BP levels here were pretreatment or basal levels.…”
Section: Pooled Predictive Accuracy Of Wfa+-m2bp In Liver Fibrosismentioning
confidence: 99%